Film Tourism and Transmedia Storytelling: Exploring Yogyakarta’s Heritage - Santyaputri, Lala (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study investigates how film tourism and transmedia storytelling contribute to meaningful and memorable cultural experiences in Yogyakarta, Indonesia. Using a qualitative design, 25 interviews with filmmakers, tourism officials, and film tourists were analyzed with thematic coding in NVivo 14. Three core themes emerged: immersive experience, visual appreciation, and cultural enrichment. NVivo used to organize interview transcripts, identify themes, and cross-analyze stakeholders' responses. This study finds that transmedia storytelling—through social media, cinematic landscapes, and on-site interpretation—amplifies audience engagement with cultural heritage. The convergence of business storytelling and art history presents both challenges and opportunities. NVivo analysis allowed for deeper insight into how location-based storytelling is processed cognitively and emotionally by audiences, thus highlighting film's capacity as an educational and promotional tool in heritage tourism. The assessment concludes that film tourism combined with transmedia storytelling is an effective strategy for promoting destination recognition and preserving local heritage by offering immersive, culturally rich, and engaging tourism experiences through cinematic narratives, interactive media, and collaborative storytelling practices.